The Petroleum Exploitation and Pollution in Ogoni, Rivers State, Nigeria: The Community Perspective - Tombari Bodo; Lekpa Kingdom David (European Scientific Journal, ESJ, 2018)
The aim of this paper was to examine community perspective to petroleum exploitation and pollution in Ogoni, Rivers State. To achieve this aim, the objective was to determine the extent to which the pollution of the environment has affected the people’s views of usefulness of the resources in their communities. The survey design method was employed. Purposive sampling technique was used to select 21 oil bearing communities from the four Local Government Areas (LGAs) of Ogoniland. The data were collected using interviews, focus group discussions, oral testimonies and questionnaires. Being qualitative; transcriptions, rewriting and coding were employed in data analysis, except for the questionnaires which adopted descriptive statistical methods. Results showed that majority of the people have not benefitted from the petroleum resources in their communities. It was revealed that pollution has changed the people’s views of the usefulness of petroleum resources, as they clearly see the resources in their communities as a curse. However, many communities believed that there was no sincerity on the part of their leaders, as the dividends claimed to be given by the multinational oil companies (MNOCs) for the welfare and benefit of the people were not visible. It is recommended that in order to change the perception of the people toward petroleum exploitation, the MNOCs should massively develop the host communities with basic social amenities and deal directly with the land owners whose portions of land are directly affected and not through the chiefs or the Community Based Organisations (CBOs).